2021
DOI: 10.1111/bju.15399
|View full text |Cite
|
Sign up to set email alerts
|

How reliable are surgeon‐reported data? A comparison of the British Association of Urological Surgeons radical prostatectomy audit with the National Prostate Cancer Audit Hospital Episode Statistics‐linked database

Abstract: To evaluate the accuracy and completeness of surgeon-reported radical prostatectomy outcome data across a national health system by comparison with a national dataset gathered independently from clinicians directly involved in patient care. Patients and MethodsData submitted by surgeons to the British Association of Urological Surgeons (BAUS) radical prostatectomy audit for all men undergoing radical prostatectomy between 2015 and 2016 were assessed by cross linkage to the National Prostate Cancer Audit (NPCA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Although this might be considered a limitation, pragmatically local treatment decisions were being based on the measurements reported in the study and as such we believe the results presented are of value to practicing urologist. Previous surgical audits have demonstrated that surgeon collected data is accurate [21]. Furthermore this study contributes data on BOO outcomes in a large cohort of men without being compromised by surgeon equipoise.…”
Section: Discussionmentioning
confidence: 82%
“…Although this might be considered a limitation, pragmatically local treatment decisions were being based on the measurements reported in the study and as such we believe the results presented are of value to practicing urologist. Previous surgical audits have demonstrated that surgeon collected data is accurate [21]. Furthermore this study contributes data on BOO outcomes in a large cohort of men without being compromised by surgeon equipoise.…”
Section: Discussionmentioning
confidence: 82%
“…In studies that do report this, long‐term outcomes are usually lacking. Future studies could first focus on collecting these data more robustly in a national registry, as is performed in the UK for other urological conditions [9–11].…”
Section: Discussionmentioning
confidence: 99%
“…Aning et al recently validated BAUS radical prostatectomy data against National Prostate Cancer Audit data, indicating good agreement for operative and histological data fields. 13 One might consider that comparable data for cystectomy are likely to be similarly accurate, although this has not been tested.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 471 patients constituted 20.4% (471/2309) of all patients reported as having muscle-invasive TCC. Median LOS for patients on ERAS pathways was 9 days (IQR 6-14) compared with 13 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) for those not recovered using ERAS pathways. Amongst patients managed using an ERAS pathway the return to theatre (RTT), unplanned high-dependency unit (HDU) admission and unplanned hospital readmission rates were 3.3%, 1.6% and 11.2% respectively, compared with 7.6%, 2.5% and 13.8% respectively for patients not managed using an ERAS pathway.…”
Section: Nacmentioning
confidence: 99%